The silence of the girls - Barker, Pat 1943- (Penguin Books, 2019)
"From the Booker Prize-winning author of the Regeneration trilogy comes a monumental new masterpiece, set in the midst of literature's most famous war. Pat Barker turns her attention to the timeless legend of The Iliad, as experienced by the captured women living in the Greek camp in the final weeks of the Trojan War. The ancient city of Troy has withstood a decade under siege of the powerful Greek army, who continue to wage bloody war over a stolen woman--Helen. In the Greek camp, another woman watches and waits for the war's outcome: Briseis. She was queen of one of Troy's neighboring kingdoms, until Achilles, Greece's greatest warrior, sacked her city and murdered her husband and brothers. Briseis becomes Achilles's concubine, a prize of battle, and must adjust quickly in order to survive a radically different life, as one of the many conquered women who serve the Greek army.
Keywords: Trojan War; Briseis (Legendary character) / Fiction; Trojan War / Fiction; Troy (Extinct city) / Fiction; Briseis (Legendary character); Turkey / Troy (Extinct city); Briseis (Legendary character) - Fiction; Trojan War - Fiction; Troy (Extinct city) - Fiction; Historical fiction; War stories; Fiction; Fiktionale Darstellung